Radiation-induced inflammatory responses in carcinogenesis and cardiac disease - Shigemori, K (2022)
More than half of cancer patients receive radiotherapy in the course of their treatment. Recently, clinical and preclinical studies have indicated that radiation may have anti-cancer effects through the initiation of tumour-specific immune responses in addition to tumour cell-intrinsic DNA-damage. The role of the tumour microenvironment in cancer development, progression and response to therapy is increasingly being recognised. However, few pre-clinical models are available for the co-evaluation of tumour and normal tissues in response to radiation therapy. The aims of this thesis are: (1) to establish a pre-clinical mouse model which can be used to evaluate tumour and normal tissue responses to cancer therapies; (2) to dissect the critical biological processes in carcinogen-induced lung tumour initiation and development (with a focus on immune and stromal context); and (3) to investigate the mechanisms important in radiation-induced normal tissue responses in cardiac and lung tissues.